2019
DOI: 10.1002/pat.4615
|View full text |Cite
|
Sign up to set email alerts
|

Influence of graphene nanoscrolls on the crystallization behavior and nano‐mechanical properties of polylactic acid

Abstract: Graphene nanoscrolls (GNS), one‐dimensional carbon‐based nanomaterials, have been predicted to possess extraordinary characteristics due to their unique open topology with scrolled graphene monolayers. In this study, the conversion of planar 2‐D graphene nanoplatelets (GNPs) to tubular and scrolled 1‐D GNSs is described. The effects of GNS as a nucleating agent to modulate the morphology, crystallization, and nano‐mechanical properties of polylactic acid (PLA) were studied. The nucleating effect of GNS and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…The micromechanical properties of unmodified PLA have been very rarely tested using the instrumented indentation method [ 49 , 50 ] and, to the best of our knowledge, so far no one has tested surface-modified PLA. Microhardness and elastic modulus of neat and extruded PLA were tested using a diamond Berkovich indenter with indentation load of 0.5 mN, resulting in the maximum indentation depths of, respectively, 1.5 µm and [ 49 ] 1 µm [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The micromechanical properties of unmodified PLA have been very rarely tested using the instrumented indentation method [ 49 , 50 ] and, to the best of our knowledge, so far no one has tested surface-modified PLA. Microhardness and elastic modulus of neat and extruded PLA were tested using a diamond Berkovich indenter with indentation load of 0.5 mN, resulting in the maximum indentation depths of, respectively, 1.5 µm and [ 49 ] 1 µm [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The micromechanical properties of unmodified PLA have been very rarely tested using the instrumented indentation method [ 49 , 50 ] and, to the best of our knowledge, so far no one has tested surface-modified PLA. Microhardness and elastic modulus of neat and extruded PLA were tested using a diamond Berkovich indenter with indentation load of 0.5 mN, resulting in the maximum indentation depths of, respectively, 1.5 µm and [ 49 ] 1 µm [ 50 ]. The elastic modulus of extruded PLA ranged from 3.9 ± 0.47 GPa on specimen edges to 4.1 ± 0.26 GPa in the middle of the specimen, while modulus and hardness of neat PLA were uniform and equal to 4.6 ± 0.47 GPa and 0.23 ± 0.034 GPa, respectively [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nanoindentation is commonly used to mechanically characterize polymers and polymer nanocomposite thin films . The nanoindentation experiments were performed using an Agilent G200 nanoindenter by MTS instruments equipped with a Berkovich three‐sided tip with tip radius of 100 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The nucleating agent can instantaneously increase the nucleation density in PLLA matrix and reduce the surface free energy barrier to induce the crystallization to occur in the higher temperature region or at a faster cooling rate. As a result, the crystallization of PLLA has been improved by a large amount of effective nucleating agents such as talc [12], montmorillonite [13], mica [14], halloysite [15], calcium carbonate [16], zinc citrate [17], silicon dioxide [18], grapheme [19], YVO4 [20], metal phosphonate [21], zinc salts of amino acids [22], metallic salts of phenylmalonic acid [23], p-tert-butylcalix [8]arene [24], myo-inositol [25], sorbitol derivative [26,27], fulvic acid amide [28], benzoyl hydrazine derivatives [29,30], 1H-benzotriazole derivatives [31], etc. Through analysis of progress in nucleating agents for PLLA, it was found that the nucleating agent for PLLA gradually evolved from inorganic compounds to organic compounds [32].…”
Section: Introductionmentioning
confidence: 99%